Air pollution and asthma control in the Epidemiological study on the Genetics and Environment of Asthma. Issue 9 (20th June 2011) - Jacquemin, Bénédicte; Kauffmann, Francine; Pin, Isabelle; Le Moual, Nicole; Bousquet, Jean; Gormand, Frédéric; Just, Jocelyne; Nadif, Rachel; Pison, Christophe; Vervloet, Daniel; Künzli, Nino; Siroux, Valérie; et al.
Abstract : Background: The associations between exposure to air pollution and asthma control are not well known. The objective of this study was to assess the association between long-term exposure to NO2, O3 and PM10 and asthma control in the follow-up of the Epidemiological study on the Genetics and Environment of Asthma (EGEA2) (2003–2007). Methods: Modelled outdoor NO2, O3 and PM10 estimates were linked to each residential address using the 4 km grid air pollutant surface developed by the French Institute of Environment in 2004. Asthma control was assessed in 481 subjects with current asthma using a multidimensional approach following the 2006–2009 Global Initiative for Asthma guidelines. Multinomial and ordinal logistic regressions were conducted adjusted for sex, age, body mass index, education, smoking and use of inhaled corticosteroids. The association between air pollution and the three domains of asthma control (symptoms, exacerbations and lung function) was assessed. ORs are reported per IQR. Results: Median concentrations (in micrograms per cubic metre) were 32 (IQR 25–38) for NO2 (n=465), 46 (41–52) for O3 and 21 (18–21) for PM10 (n=481). In total, 44%, 29% and 27% had controlled, partly controlled and uncontrolled asthma, respectively. The ordinal ORs for O3 and PM10 with asthma control were 1.69 (95% CI 1.22 to 2.34) and 1.35 (95% CI 1.13 to 1.64), respectively. When including both pollutants in the same model, both associations persisted. Associations were not modified by sex, smoking status, use of inhaled corticosteroids, atopy, season of examination or body mass index. Both pollutants were associated with each of the three main domains of control. Conclusions: The results suggest that long-term exposure to PM10 and O3 is associated with uncontrolled asthma in adults, defined by symptoms, exacerbations and lung function.